IMPLIKATUR PERCAKAPAN DALAM KUMPULAN CERPEN PILIHAN KOMPAS 2014 - Sari, Hazizah Mega; Patriantoro, Patriantoro; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to describe the meaning of conversational implicature, the type of conversation implicatures and the form of conversational implicature. A short story of compass selection is the best short story written by famous writers and through the screening stage conducted by five jurors who have been competent in their field.This research method was a descriptive method. This research was qualitative using documentary study technique. Data in this research in the form of conversation sentences that contained conversational implicatures in a collection of short stories Kompas 2014 data sources in this study were short stories contained in a collection of Short Selection Kompas 2014.The results of this study got 41 conversational implicatures from 13 short stories contained figurative meanings, emotive meanings, affective meanings, and pictorial meanings. Figurative meaning consists of 26 meanings, emotive meaning consists of 5 meanings, affective meaning consisted of 8 meanings, and the meaning pictorial consists of 2 meanings. There were 3 forms of implicature sentences, ie news sentences, sentence, and sentence commands. The news sentence consists of 28 sentences, 13 sentence sentences, and a command sentence consisted of 6 sentences. There were two types of conversational implicatures namely, general conversational implicatures and special conversation implicatures. Â Keywords: Conversation Implicature, Implicature Meaning, Implicature Type